SUBJECTIVE AGE BIAS AS A PSYCHOLOGICAL PROTECTIVE FACTOR IN THE AGING PROCESS. (11th November 2018) - Grah, S; Dzierzewski, J; Ravyts, S; Raldiris, T; Perez, E
Abstract: Subjective age bias (the difference between chronological age and felt age) has been explained as a protective factor that allows aging individuals to psychologically distance themselves from "older adults" as a group, thereby also distancing themselves from negative age-related identity threats like stereotyping and discrimination that can decrease current life satisfaction. To test this model, the current study aims to examine the moderating role of experiences of discrimination in the relationship between chronological age and subjective age bias. This study also examined self-esteem as an explanatory factor by which adopting a more exaggerated subjective age bias is associated with greater life satisfaction. The aims were addressed using a nationwide sample of older adults (N=3, 294, Mean age = 64) from the third wave of the National Midlife in the United States study (MIDUS III). Moderation analyses confirmed that advancing chronological age is associated with a greater subjective age bias, and that this pattern is exaggerated for participants who experience higher levels of discrimination. Mediation analysis supported the hypothesis that greater subjective age bias in this sample was associated with higher life satisfaction, and that this relationship was partially explained by higher levels of self-esteem. These results suggest that increasing subjective age bias with age may operate to protect psychological well-being in the face of discrimination, a benefit partially explained by greater self-esteem. Future research should investigate the modifiability of subjective age in order to increase life satisfaction and other factors related to psychological well-being as people age.